2019
DOI: 10.26504/qec2019spr_sa_fahy
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the implications of monetary policy normalisation for Irish mortgage arrears

Abstract: The current level of the monetary policy rate in the Eurozone is low both by international and historical standards and will likely rise over the coming years. In this Article we consider what the impact of a rise in ECB policy rates would mean for the Irish mortgage market. First, we examine the structure of the Irish mortgage market in terms of interest rate contract types and explore the link between the mortgage rate and the policy rate. Second, we draw out the results of policy modelling linking arrears a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…In addition, they express sample selection concerns, arguing that certain households may be less willing to answer survey questions and that this is likely correlated with them having repayment diculties, leading to underrepresentation of mortgage default in surveys. In previous work using SILC Slaymaker et al (2019) have shown that for the period 2009-2016 1 , there is a 0.88 correlation between McCann (2017) shows that the actual six monthly ow was approximately 1.5%, indicating that the model based on these SILC data is a very close t with the actual observed loanlevel data. We therefore contend that SILC is a suitable dataset with which to undertake analysis of the determinants of mortgage default.…”
Section: Data and Summary Statisticsmentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, they express sample selection concerns, arguing that certain households may be less willing to answer survey questions and that this is likely correlated with them having repayment diculties, leading to underrepresentation of mortgage default in surveys. In previous work using SILC Slaymaker et al (2019) have shown that for the period 2009-2016 1 , there is a 0.88 correlation between McCann (2017) shows that the actual six monthly ow was approximately 1.5%, indicating that the model based on these SILC data is a very close t with the actual observed loanlevel data. We therefore contend that SILC is a suitable dataset with which to undertake analysis of the determinants of mortgage default.…”
Section: Data and Summary Statisticsmentioning
confidence: 77%
“…Previous descriptive work by Fahy et al (2018) using Irish SILC data provides suggestive evidence that the relative importance of the various channels of default may vary over time. They show that during pre-crisis years households that suered health, employment and marital shocks saw higher mortgage default rates 3 , but that during the systemic crisis typically lower risk groups such as the employed and healthy saw the largest increases in incidence of default.…”
Section: Does the Level Of Indebtedness Matter?mentioning
confidence: 91%
See 3 more Smart Citations